Change In Shrinkage Of Aluminum Alloy During Crystallization As A Result Of Alloy Modification - Nigora Rizaeva; Sarvar Tursunbaev (Stanford Database Library of American Journal of Applied Science and Technology, 2026)
Aluminum alloys differ from other non-ferrous alloys due to their high casting properties. This article analyzes the effect of modification of aluminum alloys on their shrinkage. The studies were carried out on alloys of the aluminum–silicon and aluminum–copper systems. These alloys were modified with lithium fluoride, and changes in their shrinkage were investigated. Based on the conducted experiments and tests, a relationship between the shrinkage of aluminum alloys and the amount of modifying additive was established. The article also presents the authors’ conclusions drawn from the obtained results.